Relationship analysis between HRM practices and core competencies: Field research on a sample of workers in the Ministry of Construction and Housing, Municipalities and Public Works - جثير سعدون حمود; جهاد عدي صلاح (Journal of Economics and Administrative Sciences, 2025)
The main objective of the research is to analyze the correlation between human resource management practices and the basic capabilities. The research was carried out in the practical part of the Ministry of Construction, Housing, Municipalities and Public Works. Human Resources are the most important resources owned by the Organization. And other resources, but they cannot use them efficiently and effectively without the presence of human resources with rare, unique and unmatched natural resources by competitors, the organization is able to guide and exploit The focus on the core competencies of the future includes the ability and the ability to defend and attack at the same time to deal with the changing environment as a characteristic of the age. In particular, the consequences of this environmental change require an assessment. The improvement or enhancement of the core competencies, which leads to meet the requirements of the beneficiaries of the services provided by the Ministry of Construction, Housing, Municipalities and Public Works. In this framework, the research sample included the employees of the Ministry (132) The questionnaire has been used as a data collection tool, and the research has found a correlation between human resources management practices and core competencies.